A Rare Cause of Weight Loss in Immunocompetent Subject - Nasa, Mukesh; Gupta, Mahesh; Bhansali, Shashank; Lipi, Lipika; Puri, Rajesh (Journal of Digestive Endoscopy, 2019)
We report a case of 61-year-old immunocompetent man with no comorbidity presenting with unexplained weight loss. All routine investigations could not point to the etiology of weight loss, but duodenal biopsy taken on upper gastrointestinal endoscopy revealed larvae of Strongyloides stercoralis, a nematode endemic to Indian subcontinent. The patient recovered after course of albendazole, and in the absence of other causality, weight loss was attributed to strongyloidiasis.
Keywords: edema; Strongyloides stercoralis; weight loss